GELIAT RUANG SENI DAN KREATIVITAS DI SANGGAR SENI PEKANDELAN AGUNG - I Putu Bagus Restu Pratama Wiwaha; I Wayan Mudra; I Ketut Sariada (UHN IGB Sugriwa Denpasar, 2025)
Pekandelan Agung Art Studio is an art studio that continues to preserve traditional dance arts amidst the influx of foreign cultures into Indonesia. This study aims to analyze the activities of Pekandelan Agung Art Studio in preserving traditional Balinese dance arts in 2019-2025. Data collection methods were carried out through observation, interviews, and documentation, determining data sources with purposive sampling and data analysis with hermeneutics. The results of the study showed that the activities of Pekandelan Agung Art Studio in preserving traditional Balinese dance arts were carried out through dance education, dance training, and performances internally and externally as well as building social, cultural, and economic values. The positive activities of this studio received the